2000
DOI: 10.2172/771285
|View full text |Cite
|
Sign up to set email alerts
|

Final report, DOE-EPsCoR Grant No. DE-FG02-99ER45754: Removal of organic contaminants from water via spray processes

Abstract: Introduction:This project was funded for a total of $92,946 for the period from 2/16/99 to 2/15/01. We studied extraction efficiency of organic substances from water matrices using spray chambers that were designed and constructed in our laboratories. A number of parameters that were hypothesized to affect the rate of removal of these compounds were studied, ineIuding chamber volume, extraction gas flow rate, sample volume, temperature, chamber pressure, physical and chemical properties of the analytes, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…33 However, different patterns of MSS adsorption were observed in the filter of the 3R4F compared to little cigars after smoking under ISO conditions (Figures SI6–8 in the Supporting Information). Ventilation holes were found in the filter paper of the 3R4F, whereas no holes were detected in any of the filter papers of the selected little cigars (Figure SI5).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…33 However, different patterns of MSS adsorption were observed in the filter of the 3R4F compared to little cigars after smoking under ISO conditions (Figures SI6–8 in the Supporting Information). Ventilation holes were found in the filter paper of the 3R4F, whereas no holes were detected in any of the filter papers of the selected little cigars (Figure SI5).…”
Section: Resultsmentioning
confidence: 98%
“…5,10,18–20 Previous studies have examined the effect of different physical properties and smoking regimens on the levels and toxicity of the MSS HPHCs across different brands of cigarettes. 3,10,19,33,42,43,45,46 To understand how these variables in cigarettes are different from little cigars, we compared the physical properties of the most popular little cigars 27,28 with the 3R4F. Our results showed that each of the selected little cigars are longer (~15 mm), and therefore, hold more tobacco mass (100–200 mg), than the 3R4F.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation